PERSEPSI WISATAWAN MANCANEGARA TENTANG KUALITAS PELAYANAN FRONT DESK AGENT HOTEL BERBINTANG EMPAT DI KOTA PADANG - Morito, Dede; Silfeni, Silfeni; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of research is to determine the foreign tourists’ perceptions about the quality of service of front desk agent four star hotels in Padang. This research consists of five indicators are: tangibles, reliability, responsiveness, assurance, and epathy. The type of this research is descriptive research using survey method with population amounted to 310 people. Sampling technique is proportional random sampling with sample amounted to 76 people. The data was collected using a questionnaire based on a Likert scale that tested for validity and reliability. Based on the results of the study concluded that the foreign tourists’ perceptions about quality of service of front desk agent four star hotels in Padang are less in two indicators, assurance and empathy.